Polymorphism of the precursor for the major surface antigens of Plasmodium falciparum merozoites: studies at the genetic level. - Mackay, M (1985)
The gene for the precursor of Plasmodium falciparum merozoite surface antigens has been cloned. The entire sequence of the gene from a Thai isolate of the parasite is reported. It provides evidence for a signal peptide, a region containing short repeating peptides and an anchor sequence. In addition, the 5' end of a Papua New Guinea isolate has been sequenced. Comparison of these and other sequences defines, at the genetic level, a polymorphic region in the protein, and suggests that other parts of the protein are less susceptible to variation. Furthermore it appears that several signal peptides of P. falciparum exhibit extensive sequence homologies.